Methods for manufacturing the negative electrode and methods for manufacturing energy storage devices
Patent Information
- Application Number
- CN202610331725.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-03-19
- Filing Date
- 2026-03-18
- Publication Date
- 2026-09-22
AI Technical Summary
[0008]According to the research of the inventors, the aforementioned "blackness" serves as an indicator of the load applied to the negative electrode slurry during mixing, and is considered to be related to the amount of gas (bubbles) generated. Furthermore, the aforementioned "viscosity" serves as an indicator of the coatability of the negative electrode slurry. By setting the blackness and viscosity of the negative electrode slurry to the aforementioned ranges, it is possible to stably coat negative electrode slurries with minimal bubble incorporation, thereby improving coating defects caused by bubble incorporation.
Smart Images

Figure CN122800558A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for manufacturing a negative electrode and a method for manufacturing an energy storage device. Background Technology
[0002] Typically, the negative electrode of an energy storage device has a structure in which a negative electrode composite material layer containing a negative electrode active material is supported on a negative electrode current collector. Such a negative electrode is made, for example, by mixing the negative electrode active material and other materials of the negative electrode composite material layer in water to prepare a slurry, and then coating the prepared slurry onto the negative electrode current collector (see, for example, Patent Documents 1 and 2).
[0003] Patent Document 1: Japanese Patent Application Publication No. 2023-096785
[0004] Patent Document 2: Japanese Patent Application Publication No. 2020-113485 Summary of the Invention
[0005] In recent years, from the perspective of increasing capacity, the use of Si-containing materials as negative electrode active materials has been studied. However, according to the research of the inventors, Si-containing materials have high reactivity with water. Therefore, if the Si-containing material breaks due to the mixing load during slurry preparation, gas (typically hydrogen) is easily generated on the newly formed surface. As a result, air bubbles are mixed into the slurry, which easily leads to poor coating.
[0006] The present invention was made in view of the above circumstances, and its object is to provide a method for manufacturing a negative electrode that can improve poor coating caused by air bubbles.
[0007] According to one aspect of the present invention, a method for manufacturing a negative electrode is provided, comprising: a preparation step of mixing graphite, a Si-containing material, a binder, and a fibrous carbon material as negative electrode active materials in a dispersion medium containing at least water to prepare a negative electrode slurry; and a coating step of coating the negative electrode slurry onto a negative electrode current collector to form a negative electrode composite material layer. Specifically, after mixing the negative electrode slurry with 10 times its mass of ion-exchanged water and centrifuging, the supernatant is collected and diluted with ion-exchanged water to 5 times its volume to obtain a sample. In the absorption spectrum of the sample measured at an optical path length of 25 mm, the sum of the absorbance at wavelengths of 600 nm, 700 nm, 800 nm, and 900 nm multiplied by 5 is taken as the blackness. In the preparation step, the negative electrode slurry is prepared to have a blackness of 30-65 and a shear rate of 100 s. -1 The viscosity at that time was below 1100 mPa·s.
[0008] According to the research of the inventors, the aforementioned "blackness" serves as an indicator of the load applied to the negative electrode slurry during mixing, and is considered to be related to the amount of gas (bubbles) generated. Furthermore, the aforementioned "viscosity" serves as an indicator of the coatability of the negative electrode slurry. By setting the blackness and viscosity of the negative electrode slurry to the aforementioned ranges, it is possible to stably coat negative electrode slurries with minimal bubble incorporation, thereby improving coating defects caused by bubble incorporation. Attached Figure Description
[0009] Figure 1 This is a flowchart of a manufacturing method involved in one implementation.
[0010] Figure 2 This is a graph showing the relationship between the viscosity and blackness of the negative electrode slurry.
[0011] Figure 3 This is a graph showing the relationship between the blackness of the negative electrode slurry and the amount of gas generated.
[0012] Symbol Explanation
[0013] S10 preparation process
[0014] S11 Dry Mixing Process
[0015] S12 Wetting Process
[0016] S13 Mixing Process
[0017] S14 Dilution process
[0018] S20 coating process Detailed Implementation
[0019] The preferred embodiments of the technology disclosed herein will now be described. In this specification, matters necessary for implementing the technology disclosed herein (e.g., the general structure and manufacturing process of an energy storage device without the technical features disclosed herein), except as specifically mentioned, can be understood as design matters performed by those skilled in the art based on existing technology. The technology disclosed herein can be implemented based on the content disclosed in this specification and common technical knowledge in the art.
[0020] It should be noted that in this specification, "energy storage device" is a general term for devices capable of repeated charging and discharging. It includes not only secondary batteries such as lithium-ion batteries and nickel-metal hydride batteries, but also capacitors such as double-layer capacitors, lithium-ion capacitors, and pseudocapacitors. Furthermore, in this specification, the expression "A~B" indicating a range means above A and below B, and includes both "preferably greater than A" and "preferably less than B".
[0021] [Method for manufacturing the negative electrode]
[0022] Figure 1 This is a flowchart illustrating a manufacturing method involved in one implementation. For example... Figure 1 As shown, the method for manufacturing the negative electrode disclosed herein sequentially includes: a preparation step of preparing a negative electrode slurry (step S10), and a coating step of coating the negative electrode slurry onto a negative electrode current collector to form a negative electrode composite material layer (step S20). Furthermore, the manufacturing method disclosed herein may further include other steps at any stage. For example, after the coating step (step S20), a pressing step of calendering the negative electrode composite material layer on the negative electrode current collector may be included. The method for manufacturing the negative electrode disclosed herein is preferably a method for manufacturing a negative electrode for a secondary battery, and more preferably a method for manufacturing a negative electrode for a lithium-ion secondary battery.
[0023] The preparation process (step S10) is a process of mixing (1) the negative electrode active material, (2) the binder and (3) the fibrous carbon material in a dispersion medium containing at least water to prepare a specified negative electrode slurry (including paste and ink). Hereinafter, the materials (1) to (3) mentioned above used here will be described first.
[0024] (1) The negative electrode active material is a material that can reversibly absorb and release charge carriers. In this embodiment, the negative electrode active material must contain (1a) graphite and (1b) Si-containing materials. Thus, it is possible to take into account various characteristics of the energy storage device (e.g., high capacity and high rate cycling characteristics) at a high level.
[0025] As for (1a) graphite, one or more known graphites that can be used as negative electrode active materials may be used, without particular limitation. Graphite may be natural graphite, artificial graphite, or amorphous carbon-coated graphite in the form of graphite particles as the core being coated with an amorphous carbon material.
[0026] Graphite is typically in particulate (powder) form. While not particularly limited, the average particle size of graphite (the particle size at 50% of the cumulative value in the particle size distribution based on laser diffraction-scattering (D50)) is preferably 1–100 μm, more preferably 5–50 μm, and even more preferably 10–30 μm. Graphite is typically in spherical, plate-like, or flake-like shapes. The average aspect ratio of graphite (the ratio of major to minor axis based on electron microscopy) is typically smaller than that of fibrous carbon materials described later (3), for example, 5 or less, preferably 3 or less. That is, graphite typically has a higher sphericity than fibrous carbon materials.
[0027] As for (1b) the Si-containing material, one or more known Si-containing materials that can be used as negative electrode active materials can be used, without particular limitation. Examples include Si (silicon), SiC composites, and SiO2. a(where 0.05 < a < 1.95) represents silicon dioxide, and SiC represents silicon dioxide. b (where 0 < b < 1) represents silicon carbide, and SiN represents silicon carbide. c (Where 0 < c < 4 / 3) represents silicon nitride, etc. SiC composites typically have a structure in which Si particles are arranged in cavities within a porous carbon framework. According to the research of the inventors, SiC composites are particularly prone to cracking due to the load during mixing (mixing load). Therefore, when using SiC composites, the techniques disclosed herein are particularly preferred.
[0028] Si-containing materials are typically in particulate (powder) form. While not particularly limited, the average particle size (the particle size at 50% of the cumulative value in the particle size distribution based on laser diffraction-scattering (D50)) of the Si-containing material is preferably 1–20 μm, more preferably 1–10 μm, and even more preferably 5–10 μm. Si-containing materials are typically spherical or approximately spherical in shape. The average aspect ratio (the ratio of major to minor diameter based on electron microscopy) of the Si-containing material is typically smaller than that of the fibrous carbon material described later (3), for example, it can be 3 or less, preferably 2 or less, or 1.5 or less. That is, the Si-containing material typically has a higher sphericity than the fibrous carbon material.
[0029] (2) The adhesive is a component that binds (1) the negative electrode active material and (3) the fibrous carbon (described later) together to improve the integrity of the negative electrode composite layer. There are no particular limitations on the adhesive; one or more known materials that have been previously used for this purpose may be used. Examples include rubbers such as styrene-butadiene rubber (SBR), cellulose compounds such as carboxymethyl cellulose (CMC), and acrylic resins such as polyacrylic acid (PAA) (resins obtained by polymerizing monomers having acryloyl groups). The adhesive preferably includes multiple materials, and more preferably includes SBR, CMC, and PAA simultaneously.
[0030] (3) Fibrous carbon is a component that improves the conductivity within the negative electrode composite material layer. It should be noted that, in this specification, "fibrous carbon" refers to carbon material in a fibrous (rope-like) form with an average aspect ratio (average fiber length / average outer diameter) of 10 or more. The average aspect ratio of the fibrous carbon is preferably 20 or more, more preferably 50 or more, and even more preferably 100 or more. If the average aspect ratio is above a specified value, it is easy to obtain a negative electrode composite material layer with fibrous carbon interposed between the negative electrode active material particles, and even when using the Si-containing material (1b), it is easy to form a good conductive path within the negative electrode composite material layer. The average aspect ratio of the fibrous carbon is generally preferably 100,000 or less, more preferably 50,000 or less, and may also be 10,000 or less. If the average aspect ratio is below a specified value, the amount of fibrous carbon simultaneously covering the surface of the negative electrode active material particles with the binder increases, making it easier to form a good conductive path on the surface of the negative electrode active material particles. That is, if the average aspect ratio of the carbon fibers is within the above-mentioned range, conductive pathways can be formed between the active material particles and on the surface of the active material particles, thereby further improving the conductivity within the negative electrode composite material layer. In addition, if the average aspect ratio is within the above-mentioned range, the negative electrode slurry can easily and stably meet the properties described later (especially the range of blackness), thereby easily achieving the effects of the technology disclosed herein.
[0031] The average fiber length of the fibrous carbon is typically 1.5 μm or more, but can be 1.6 μm or more, 1.7 μm or more, 1.8 μm or more, 1.9 μm or more, or 2.0 μm or more. If the average fiber length is above the specified value, it is easier to form a good conductive path within the negative electrode composite layer. The average fiber length of the fibrous carbon can be 1.5–5.0 μm, 1.8–3.0 μm, or 2.0–2.5 μm. If the average fiber length is within the above range, the negative electrode slurry can easily and stably meet the properties described later (especially the range of blackness), and easily achieve the effects of the technology disclosed herein.
[0032] It should be noted that the average fiber length and average outer diameter (average diameter) of fibrous carbon can be determined by observing multiple fibrous carbons with an electron microscope, measuring the length along the long axis and radial direction of each fibrous carbon in the obtained image, and calculating their numerical averages. More specifically, for example, multiple fibrous carbons can be observed using a scanning electron microscope (SEM) at an accelerating voltage of 1 kV to obtain SEM images. Then, the average outer diameter can be determined by measuring the radial length of multiple fibrous carbons arbitrarily extracted from the SEM image and calculating their numerical averages. Additionally, the average fiber length can be determined by using image processing software to distinguish the fibrous carbons in the SEM image by coloring them as lines, measuring the circumference of each line, taking half of the circumference as the fiber length, and calculating their numerical averages. It should be noted that the average fiber length is extremely long relative to the average outer diameter of the fibrous carbon, therefore the influence of the line width on the circumference is negligible.
[0033] The G / D ratio of the fibrous carbon, based on laser Raman spectroscopy analysis, can be 100 or less, 95 or less, 90 or less, preferably 85 or less, or 80 or less. A lower G / D ratio indicates lower crystallinity and more structural defects. This means lower strength and susceptibility to tearing under mixing load. Therefore, the technology disclosed herein is particularly preferred. The G / D ratio of the fibrous carbon can be 5 to 100, 10 to 90, or 10 to 80. If the G / D ratio is above a specified value, a good conductive path can be easily formed within the negative electrode composite layer. Furthermore, if the G / D ratio is within the above range, the negative electrode slurry can easily and stably meet the properties described later (especially the range of blackness), easily achieving the effects of the technology disclosed herein.
[0034] It should be noted that the G / D ratio of fibrous carbon is used as the value at 1590 cm⁻¹ in the Raman spectrum obtained by laser Raman spectroscopy. -1 The maximum peak intensity G of the G band appears nearby at 1350 cm⁻¹ -1 The ratio of the maximum peak intensity D of the nearby D band is used to determine the peak. The G band is a peak originating from the graphite structure, while the D band is a peak originating from structural defects. More specifically, for example, fibrous carbon is first dispersed in a dispersion medium (such as water) to prepare a dispersion, which is then transferred onto a coverslip. Next, a Raman microscope is used to irradiate a 300 μm diameter area with a laser excitation wavelength of 532 nm to obtain a Raman spectrum. Then, in the obtained Raman spectrum, the 1550–1650 cm⁻¹ range is selected as the maximum peak intensity D. -1 The maximum peak intensity within the range of 1300–1400 cm⁻¹ is set as G. -1 Let the maximum peak intensity within the range be D, and the G / D ratio can be calculated.
[0035] There are no particular limitations on the type of fibrous carbon used; one or more known materials that have been previously used for this purpose may be used. Examples include carbon nanotubes (CNTs), carbon fibers, and carbon nanofibers. Among these, CNTs are preferred due to their excellent electrical conductivity.
[0036] CNTs are fibrous carbon nanotubes with a structure of graphite rolled into a cylindrical shape forming a carbon hexagonal network. CNTs can be single-layer carbon nanotubes (SWCNTs) with one layer of graphite rolled into a cylindrical shape, multilayer carbon nanotubes (DWCNTs) with two layers of graphite rolled into a cylindrical shape, or multilayer carbon nanotubes (MWCNTs) with three or more layers of graphite rolled into a cylindrical shape. Among these, SWCNTs are preferred due to fewer structural defects and ease of achieving the aforementioned G / D ratio. CNTs may also contain impurities (e.g., catalysts, amorphous carbon) from the manufacturing process.
[0037] In this embodiment, the materials (1) to (3) above are mixed in a dispersion medium and a negative electrode slurry is prepared to meet the following two conditions: (A) the “blackness” described later is 30 to 65; (B) the shear rate is 100 s. -1 The viscosity is below 1100 mPa·s. It should be noted that in this specification, (A) blackness refers to the value measured as follows: First, the negative electrode slurry is mixed with 10 times its mass of ion-exchanged water and centrifuged. The supernatant is collected and diluted with ion-exchanged water to 5 times its volume to obtain the sample for measurement. Next, the absorption spectrum of the obtained sample is measured at an optical path length of 25 μm. Then, the sum of the absorbance at wavelengths of 600 nm, 700 nm, 800 nm, and 900 nm in the obtained absorption spectrum is multiplied by 5 to obtain the value of (A) blackness. More specific methods for measuring (A) blackness and (B) viscosity are described in the later section on examples.
[0038] According to the research of the inventors, the (A) blackness of the negative electrode slurry is used as an indicator of the load applied to the negative electrode slurry during mixing. That is, the larger the value of (A) blackness, the greater the absorbance (in other words, the smaller the light transmittance) and the more free components there are. As mentioned above, since the (3) fibrous carbon material is fibrous, its aspect ratio is relatively large compared to the (1) negative electrode active material, and it is easily torn due to the load during mixing. Furthermore, the torn and free (3) fibrous carbon material is difficult to precipitate by centrifugation during the above-mentioned (A) blackness measurement. Therefore, it is believed that the value of (A) blackness largely depends on the amount of torn and free (3) fibrous carbon material. It is also believed that the value of blackness reflects the load applied to the negative electrode slurry during mixing.
[0039] Furthermore, as described in the experimental examples below, the inventors have discovered that the blackness of the negative electrode slurry (A) is negatively correlated with the amount of gas (bubbles) generated. Therefore, from the viewpoint of suppressing gas generation and preparing a negative electrode slurry with less bubble incorporation, it is preferable to adjust the mixing load in this process to achieve a blackness of (A) of at least a specified value. Although not intended to be particularly limiting, the reason for reducing bubble incorporation by setting the blackness of (A) to at least a specified value can be considered as follows: (1b) The Si-containing material is a material that is easily broken by the mixing load. In addition, as mentioned above, since the (1b) Si-containing material is highly reactive with water, if the mixing load causes the Si-containing material to break, gas (typically hydrogen) is easily generated on the new surface. However, if a large amount of free fibrous carbon exists around the exposed new surface when the Si-containing material breaks due to the mixing load, the new surface is easily and quickly covered by the free fibrous carbon. Therefore, while the Si-containing material is moderately damaged, recombination with free fibrous carbon is easily achieved. It can be argued that by coating the surface of the Si-containing material with free fibrous carbon and then recombinating it, the exposure of new surfaces can be prevented. Furthermore, it is believed that the generation of gas (bubbles) can be suppressed.
[0040] Furthermore, the viscosity (B) of the negative electrode slurry is used as an indicator of coatability (ease of coating, formation stability, etc.) in the coating process (step S20), and its correlation with (A) blackness or mixing load has been confirmed. Therefore, from the viewpoint of stably coating the negative electrode slurry, it is preferable to set the viscosity (B) to a specified value or below. By setting the blackness and viscosity of the negative electrode slurry to the above ranges respectively, a negative electrode slurry with low bubble inclusion and excellent coatability can be stably prepared.
[0041] In this embodiment, this process includes at least a mixing process. By adjusting the load on the negative electrode slurry during the mixing process, and more specifically by adjusting the mixing method and mixing conditions, the (A) blackness and (B) viscosity of the negative electrode slurry can be adjusted. Figure 1 As shown, this process sequentially includes a dry mixing step (step S11), a wetting step (step S12), a kneading step (step S13), and a dilution step (step S14). However, in other embodiments, steps other than the kneading step, such as the dry mixing step and the wetting step, may be appropriately omitted. Furthermore, this process may further include other steps at any stage.
[0042] In each process, as long as the (A) blackness and (B) viscosity of the negative electrode slurry meet the above ranges, one or more previously known mixing or kneading methods may be appropriately used. Mixing or kneading can be carried out, for example, using a multi-shaft kneader such as a twin-shaft kneader, a single-shaft kneader, a planetary mixer, a disperser, a ball mill, a jet mill, a mortar and pestle, a spatula, etc. It should be noted that the following will take the use of SBR, CMC and PAA as (2) binders as examples to describe each process in detail.
[0043] The dry mixing process (step S11) is a process in which powdered materials are premixed to obtain a first powdered mixture. Specifically, the prepared graphite (1a) and Si-containing material (1b) as (1) negative electrode active materials, and powdered CMC and PAA as (2) binders are weighed to achieve a specified mass ratio, and then mixed by a dry mixing method (dry mixing). This improves the homogeneity or integrity of the negative electrode composite material layer.
[0044] Although not specifically limited, the mixing ratio of (1a) graphite and (1b) Si-containing material is preferably graphite:Si-containing material = 95:5 to 40:60, more preferably 90:10 to 60:40. (1) In the negative electrode active material, graphite is preferably the first component (the component with the largest mass percentage, the same below), more preferably graphite is the main component (the component accounting for more than 50% by mass, the same below). In addition, when the total amount of (1) negative electrode active material is set to 100% by mass, the content of (1a) graphite is preferably 50 to 95% by mass, more preferably 60 to 90% by mass. When the total amount of (1) negative electrode active material is set to 100% by mass, the content of (1b) Si-containing material is preferably 5 to 50% by mass, more preferably 10 to 30% by mass.
[0045] While not specifically limited, the total of (1a) graphite and (1b) Si-containing material preferably accounts for 80% or more by mass of the total (1) negative electrode active material, more preferably 90% or more by mass, and even more preferably 95% or more by mass. It may also be substantially composed of (1a) graphite and (1b) Si-containing material (the total of the two components may account for 98% or more by mass). However, the negative electrode active material may typically further include other known negative electrode active material materials that can be used as negative electrode active materials in a proportion less than that of (1a) graphite and (1b) Si-containing material. The proportion of other negative electrode active material materials is preferably 10% or less by mass of the total negative electrode active material, more preferably 5% or less by mass.
[0046] Although not particularly limited, when the (1) negative electrode active material is set to 100 parts by mass, the ratio of CMC and PAA as the (2) binder is preferably 0.1 to 5 parts by mass, more preferably 0.5 to 4 parts by mass, and even more preferably 1 to 3 parts by mass.
[0047] It should be noted that the dry mixing process does not contain a dispersion medium (e.g., water) and (3) fibrous carbon. Therefore, according to the research of the inventors, the effect of this process on the properties of the negative electrode slurry, particularly (A) blackness and (B) viscosity, is minimal compared to subsequent processes (steps S12-14). Therefore, the dry mixing method and mixing conditions for this process can be the same as before, without particular limitation. In one example, a planetary mixer is used, typically with light mixing at a speed lower than that of subsequent processes (steps S12-14) (e.g., 15 rpm). The mixing time is approximately within 1 hour, preferably within 30 minutes (e.g., about 10 minutes).
[0048] The wetting process (step S12) is a process in which the powdered first mixture obtained in the dry mixing process (step S11) is mixed with (3) fibrous carbon and a dispersion medium containing water to obtain an initial slurry. In some embodiments, it is preferable to pre-disperse (3) fibrous carbon in a dispersion medium (e.g., water) and add it in the form of a dispersion. In addition, the dispersion medium is typically water, but it may also be a mixed solvent containing one or more organic solvents that are mixed with water. As the organic solvent that is mixed with water, organic solvents that are uniformly mixed with water, such as alcohols, ethers, ketones, lower carboxylic acids, etc., can be used. In the dispersion medium, it is preferable that water is the main component (50% by mass or more), more preferably 80% by mass or more, further preferably 95% by mass or more, and particularly preferably substantially composed of water (98% by mass or more). The dispersion medium (e.g., water) is preferably added such that the solid content (NV value: Non-Volatile) of the initial slurry, in other words, the solid content during the mixing process (step S13), is approximately 50% by mass or more, preferably 55% by mass or more, for example 55 to 65% by mass, and more preferably 62% by mass or less. By setting the solid content of the initial slurry within the above range, a suitable mixing load (shear force) can be applied to the slurry in the mixing process (step S13) described later, making it easy and stable to prepare a negative electrode slurry with the desired properties (especially blackness). In addition, a homogeneous negative electrode slurry is easily obtained.
[0049] Although not specifically limited, when mixing in the mixing process (step S13), if (1) the negative electrode active material is set to 100 parts by mass, the proportion of (3) fibrous carbon material is preferably 0.01 to 1 part by mass, more preferably 0.01 to 0.1 parts by mass, and even more preferably 0.05 to 0.1 parts by mass. In some embodiments, the proportion of (3) fibrous carbon material is preferably less than the proportion of (2) binder, i.e., CMC and / or PAA, added in the previous dry mixing process (step S11). By setting the proportion of (3) fibrous carbon material within the above range, it is easy to stably prepare a negative electrode slurry with the desired properties (especially blackness).
[0050] It should be noted that this step has a smaller impact on the properties of the negative electrode slurry, particularly (A) blackness and (B) viscosity, compared to the mixing step (step S13) described later. Therefore, the mixing method and conditions in this step are not particularly limited, and it is preferable not to apply excessive load to the slurry. In one example, after adding fibrous carbon and a dispersion medium (e.g., water) with an NV value within the above-mentioned range (e.g., 58–62% by mass), it is sufficient to manually mix with a spatula for about 1–5 minutes (e.g., 3 minutes). Alternatively, after adding fibrous carbon and a dispersion medium (e.g., water) with an NV value within the above-mentioned range (e.g., less than 62% by mass), it is sufficient to mix with a planetary mixer at a speed of approximately 50 rpm or less (e.g., 30 rpm) for about 1–5 minutes (e.g., 3 minutes). In this case, the speed of the planetary mixer is preferably the same as or lower than that of the subsequent steps (steps S13–14).
[0051] The mixing process (step S13) is a process of mixing (solid mixing) the initial slurry obtained in the wetting process (step S12) to obtain a mixed slurry. According to the research of the inventors, in this process, due to the strong shear force applied to the slurry, the mixing load easily leads to the cracking of powdered materials (especially (1b) Si-containing materials) or the tearing of (3) fibrous carbon. Therefore, this process has a particularly large impact on the properties of the negative electrode slurry, especially (A) blackness and (B) viscosity. Therefore, by adjusting the mixing method and mixing conditions of this process, an appropriate load can be applied to the slurry, and a negative electrode slurry with the desired properties (especially blackness) can be easily and efficiently prepared.
[0052] According to the research of the inventors, in this process, by using either of the following methods: (Method 1) mixing for a relatively short time using a multi-shaft mixer; or (Method 2) mixing for a relatively long time using a planetary mixer, the negative electrode slurry can be easily prepared to the range of (A) blackness and (B) viscosity described above. Of these, (Method 1) is more preferred because it easily and effectively utilizes the techniques disclosed herein. Furthermore, according to (Method 1), the mixing time can be shortened, thus improving productivity and operability.
[0053] In (Method 1), a multi-shaft mixer is used for relatively short-term mixing. From the viewpoint of reducing excessive damage to powdered materials (especially (1b) Si-containing materials), the mixing time is set to approximately 300 seconds or less, preferably 180 seconds or less, more preferably 90 seconds or less, and particularly preferably 70 seconds or less. From the viewpoint of applying a moderate load to powdered materials (especially (3) fibrous carbon) and uniformly mixing the slurry, the mixing time is preferably 10 seconds or more, more preferably 20 seconds or more, and even more preferably 25 seconds or more. A multi-shaft mixer typically includes a barrel (mixing chamber), shafts disposed within the barrel, and a drive mechanism for the drive shafts. Among these, a twin-shaft mixer with two shafts arranged approximately in parallel within the barrel is preferred. Rotating blades are preferably mounted on the two shafts. As a mixing condition, the distance between the edge of the rotating blade and the inner wall of the barrel (blade gap) is preferably set to approximately 0.5 to 5 mm (e.g., 1 mm).
[0054] In (Method 2), a planetary mixer is used for relatively long mixing. The mixing time, from the viewpoint of applying a moderate load to the powdered material (especially (3) fibrous carbon) and uniformly mixing the slurry, can be set to approximately 1000 seconds or more, preferably 1200 seconds (20 minutes) or more, and more preferably 1800 seconds (30 minutes) or more. From the viewpoint of reducing excessive damage to the powdered material (especially (1b) Si-containing material) and improving productivity, the mixing time is preferably 10000 seconds or less, more preferably 5400 seconds (90 minutes) or less, for example, preferably 5000 to 6000 seconds. As mixing conditions, the rotational speed of the planetary mixer is preferably approximately 100 rpm or less, more preferably 50 rpm or less (e.g., 30 to 50 rpm).
[0055] The dilution step (step S14) is a step in which the aforementioned dispersion medium (e.g., water) is further added to the mixed slurry obtained in the mixing step (step S13) to obtain a negative electrode slurry with a specified solids content (NV value). This improves the coatability in the subsequent coating step (step S20). This step also involves the further addition of a liquid (2) binder (SBR). The dispersion medium and / or binder (SBR) can be added in full at once or in multiple stages. Furthermore, the order of addition of the dispersion medium and binder (SBR) is not particularly limited. In one example, to avoid overloading the slurry, it is preferable to add the dispersion medium to the mixed slurry to bring it to a certain extent close to the specified solids content before adding the binder (SBR).
[0056] The solid content (NV value) of the negative electrode slurry is not particularly limited, but in some embodiments it is generally preferred to be 30 to 50% by mass, more preferably 35 to 45% by mass, and even more preferably 40 to 45% by mass.
[0057] It should be noted that since the solid content of the slurry decreases during the dilution process, the impact on the (A) blackness and (B) viscosity of the negative electrode slurry is considered relatively small compared to the previous mixing process (step S13). Therefore, the mixing method and mixing conditions are not particularly limited. In some embodiments, when performing a single dilution, it is preferable to add the dispersion medium to the mixed slurry in a manner that achieves a specified solid content (NV value), stir with a rotary mixer, add the binder (SBR), and then stir manually. The stirring conditions of the rotary mixer can be set, for example, to a speed of about 500 to 3000 rpm (e.g., 2000 rpm) and a stirring time of about 1 to 5 minutes (e.g., 3 minutes). The manual stirring time can be set to about 1 to 5 minutes (e.g., 3 minutes).
[0058] Alternatively, in some other embodiments, when dilution is performed in multiple stages, after each addition of the dispersion medium to the slurry, it is mixed for approximately 1 to 5 minutes (e.g., 5 minutes) using a planetary mixer at a speed of approximately 50 rpm or less (e.g., 45 rpm). Then, the binder (SBR) is added last and mixed for approximately 1 to 5 minutes (e.g., 5 minutes) at a speed of approximately 50 rpm or less (e.g., 30 rpm). Following this process, a negative electrode slurry can be prepared.
[0059] In the negative electrode slurry, when (1) the negative electrode active material is set to 100 parts by mass, the proportion of (2) the binder (here, the total proportion of CMC, PAA, and SBR) is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 8 parts by mass, and even more preferably 1 to 5 parts by mass. In some embodiments, the proportion of (2) the binder is preferably greater than the proportion of (3) the fibrous carbon material. By setting the proportion of (2) the binder within the above range, it is easy to stably prepare a negative electrode slurry with the desired properties (especially (B) viscosity).
[0060] In the negative electrode slurry, the blackness of (A) only needs to be 30 to 65, but preferably 35 or higher, more preferably 40 or higher, even more preferably 45 or higher, and particularly preferably 50 or higher. This allows for a high level of suppression of gas generation and better reduction of bubble incorporation. In some embodiments, the blackness of (A) may also be 60 or lower.
[0061] In the negative electrode slurry, the viscosity of (B) only needs to be 1100 mPa·s or less, preferably 1000 mPa·s or less, more preferably 700 mPa·s or less, and even more preferably 600 mPa·s or less. This allows for high-level suppression of poor ejection and better improvement in coating properties. In some embodiments, the viscosity of (B) is preferably 100 mPa·s or more, more preferably 200 mPa·s or more, even more preferably 300 mPa·s or more, and particularly preferably 400 mPa·s or more. This prevents the negative electrode slurry from dripping, further improving coating properties.
[0062] The coating process (step S20) is a process of coating the negative electrode slurry obtained in the preparation process (step S10) onto the negative electrode current collector to form a negative electrode composite material layer. The negative electrode current collector is preferably made of metal, and more preferably of conductive metals such as copper, copper alloys, nickel, or stainless steel. The negative electrode current collector is preferably a metal foil, and more preferably of copper foil or copper alloy foil. Although not particularly limited, the thickness of the metal foil is, for example, 5 to 35 μm, preferably 6 to 20 μm.
[0063] The negative electrode slurry can be coated onto the surface (single-sided or double-sided) of the negative electrode current collector using coating apparatus such as a gravure coating machine, slot coating machine, die coating machine, comma coating machine, or dip coating machine. The coating amount can be appropriately determined based on, for example, the solid content of the negative electrode slurry, so that the negative electrode composite material layer achieves the desired properties (thickness, etc.). In addition, since the negative electrode slurry contains a dispersion medium (e.g., water), it is preferable to dry the negative electrode composite material (i.e., the coated negative electrode slurry) to remove the dispersion medium. The drying of the negative electrode composite material can be performed in the same manner as before, for example, by heating or vacuum drying. As a result, a negative electrode composite material layer containing (1a) graphite, (1b) Si-containing material, (2) binder, and (3) fibrous carbon can be formed on the surface of the negative electrode current collector.
[0064] [Manufacturing method of energy storage device]
[0065] The energy storage device can be manufactured by, for example, a manufacturing process that includes the following steps: a manufacturing process that uses the negative electrode manufactured in the above manufacturing process to make an electrode body, and a construction process that uses the manufactured electrode body to construct the energy storage device.
[0066] In the electrode body manufacturing process, the aforementioned negative electrode is used to fabricate the electrode body. Specifically, a positive electrode and a separator are prepared separately. These can be the same as before and are not limited in any way. Then, the negative electrode manufactured by the above method is placed opposite the positive electrode via the separator. In one example, a strip-shaped positive electrode and a strip-shaped negative electrode are stacked via a strip-shaped separator and wound around a winding shaft. This fabricates the electrode body. In the assembly process, the electrode body is housed in a battery casing to construct the energy storage device. Specifically, an electrolyte is prepared separately. The electrolyte can be the same as before and is not limited in any way. The electrolyte is preferably a non-aqueous electrolyte containing a non-aqueous solvent (organic solvent) and a supporting salt (electrolyte salt). Next, the electrode body fabricated in the electrode body manufacturing process and the prepared electrolyte are housed in the battery casing. By performing the above steps, an energy storage device can be manufactured.
[0067] [Applications of energy storage devices]
[0068] Energy storage devices can be used for a variety of purposes, especially those requiring high capacity and high input / output characteristics, such as power sources (drive power supplies) for motors in passenger cars, trucks, and other vehicles. There are no particular restrictions on the type of vehicle; examples include plug-in hybrid electric vehicles (PHEVs), hybrid electric vehicles (HEVs), and battery electric vehicles (BEVs).
[0069] The following describes some test examples related to the present invention, but it is not intended to limit the present invention to these test examples.
[0070] [Preparation of negative electrode slurry]
[0071] First, prepare the materials shown in Table 1 below, and then change them. Figure 1 The conditions of the preparation process were used to prepare the negative electrode slurry (Examples 1-8, Comparative Examples 1-3).
[0072]
[0073] In Examples 1-7, firstly, the negative electrode active material (graphite and Si-containing material (SiC composite material)) shown in Table 1, along with carboxymethyl cellulose (CMC) and polyacrylic acid (PAA) as binders, were weighed to the above mass ratio. The mixture was then dry-mixed for 10 minutes at 15 rpm using a planetary mixer to obtain a powdered first mixture (dry mixing step). Next, SWCNT (in the form of a CNT dispersion, G / D ratio = 69) as fibrous carbon and a dispersion medium (water) were added to the obtained first mixture, and the NV value (58-62% by mass) was adjusted to the values shown in Table 2. The mixture was then manually mixed for 3 minutes using a spatula to obtain an initial slurry (wetting step). Next, the initial slurry was mixed using a twin-shaft mixer at a blade gap of 1 mm and a rotation speed of 900 rpm for the time shown in Table 2 (22.4-67.2 seconds) to obtain a mixed slurry (mixing step). Next, a dispersion medium (water) was added to the slurry, and it was diluted once using a rotary mixer (2000 rpm, 3 minutes). Then, styrene-butadiene rubber (SBR) was added as a binder, and the final NV value was adjusted to 42% by mass. The mixture was then manually mixed with a spatula for 5 minutes (dilution step). The negative electrode slurry was prepared according to the above steps.
[0074] In Example 8 and Comparative Examples 1-3, firstly, a powdered first mixture was obtained in the same manner as described above (dry mixing process). Next, SWCNT (in the form of a CNT dispersion) as fibrous carbon and a dispersion medium (water) were added to the obtained first mixture, and the NV value (62 or 64% by mass) was adjusted to be that shown in Table 2. The mixture was then kneaded for 3 minutes at 30 rpm using a planetary mixer to obtain an initial slurry (wetting process). Next, the initial slurry was kneaded for the time shown in Table 2 (30 minutes or 90 minutes) at 50 rpm using a planetary mixer to obtain a mixed slurry (kneading process). Next, a dispersion medium (water) was added to the mixed slurry, and a multi-stage dilution was performed five times using a planetary mixer. Specifically, after dilution, the mixture was repeatedly kneaded five times at 45 rpm for 5 minutes. Next, styrene-butadiene rubber (SBR) as a binder was added, and the final NV value was adjusted to 42% by mass. The mixture was then kneaded for 5 minutes at 30 rpm using a planetary mixer (dilution process). The negative electrode slurry was prepared according to the above method.
[0075] [Determination of viscosity of negative electrode slurry]
[0076] The viscosity of the prepared negative electrode slurry was determined using a rheometer (model: MCR102, parallel plates: PP50) manufactured by Anton Paar. Specifically, the shear rate dependence (flow curve) from 0.01 to 3170 l / s was measured at 25°C, and the viscosity value at 100 l / s was used. The results are shown in Table 2.
[0077] [Determination of the blackness of the negative electrode paste]
[0078] The prepared negative electrode slurry was mixed with 10 times its mass of ion-exchanged water. It was centrifuged at a centrifugal force of 10000G or higher for 30 minutes. The supernatant was then collected and diluted to 5 times its volume with ion-exchanged water; a portion of this supernatant was collected as a sample. The absorption spectrum of this sample was then measured using a known spectrophotometer at a path length of 25 mm. The absorbance at wavelengths of 600 nm, 700 nm, 800 nm, and 900 nm was then calculated from the obtained absorption spectrum. These absorbance values were then summed and multiplied by 5 to determine the blackness. The results are shown in Table 2. Furthermore, in... Figure 2 The figure shows the relationship between the viscosity and blackness of the negative electrode slurry.
[0079] [Determination of gas generation in negative electrode slurry]
[0080] Two g of the prepared negative electrode slurry was collected, sealed in an aluminum bag, and stored in a constant temperature bath set at 60°C for 3 days. Then, the volume before and after storage was measured using an electronic hydrometer according to Archimedes' principle. The amount of gas produced (hydrogen production) was then calculated based on the volume change before and after storage. The results are shown in Table 2. It should be noted that Table 2 shows relative values when the gas production of Comparative Example 3 is set to 100. Additionally, Figure 3 The figure shows the relationship between the blackness of the negative electrode slurry and the amount of gas generated.
[0081] [Evaluation of the coatability of the negative electrode slurry]
[0082] It was confirmed that the prepared negative electrode slurry could be continuously and stably ejected from the outlet of the slit-die coating device (model name: New Mini-100 desktop die coater) for more than 3 minutes. The results are shown in Table 2. It should be noted that in Table 2, the case of stable ejection is represented by "0", and the case of poor ejection is represented by "×".
[0083]
[0084] like Figure 2 As shown, it was confirmed that the viscosity of the negative electrode slurry is negatively correlated with its blackness. Therefore, from the viewpoint of coatability, setting the viscosity of the negative electrode slurry to 1100 mPa·s or less and the blackness of the negative electrode slurry to 65 or less is effective. Furthermore, as shown in Table 2, there were no poor ejection in Examples 1 to 8, and the coatability was excellent compared to Comparative Examples 1 to 3.
[0085] like Figure 3 As shown, a negative correlation was confirmed between the blackness of the negative electrode slurry and the amount of gas generated. That is, the higher the blackness, the more likely the gas generation will decrease. Therefore, from the perspective of suppressing gas generation, setting the blackness of the negative electrode slurry to 30 or higher is effective. Furthermore, as shown in Table 2 and... Figure 3 As shown, compared with Comparative Examples 1-3, the amount of gas produced in Examples 1-8 with a blackness of 30 or higher was less than half, indicating that the gas production was significantly suppressed.
[0086] While not intended to be particularly restrictive, this reasoning can be attributed to the influence of the degree of fracture and tearing of fibrous carbon caused by the mixing load on the Si-containing material. In other words, if a large amount of free fibrous carbon surrounds the exposed new surface when the Si-containing material fractures due to the mixing load, this new surface is easily covered by the free fibrous carbon. It can be argued that by covering the surface of the Si-containing material with free fibrous carbon in this way, the exposure of the new surface can be prevented, thus suppressing the generation of gas (bubbles).
[0087] In addition, according to Figure 3In the mixing process, the slopes of the approximate curves of Examples 1-7 using a twin-shaft mixer differ from those of Examples 8 and Comparative Examples 1-3 using a planetary mixer. Therefore, it can be seen that the optimal conditions (mixing load) for the mixing process vary depending on the mixing apparatus used. Furthermore, even with the same blackness, the amount of gas (bubbles) generated is suppressed when mixing for a relatively short time using a multi-shaft mixer in Method 1, compared to the relatively long mixing time using a planetary mixer in Method 2. For this reason, it can be considered important that when the Si-containing material breaks and the new surface is exposed, a large amount of free fibrous carbon is present, causing the new surface to be rapidly covered by fibrous carbon.
[0088] The preferred embodiments of the present invention have been described above, but these embodiments are merely examples. The present invention can also be implemented in various other ways. The present invention can be implemented based on the content disclosed in this specification and common technical knowledge in the art. The technology described in the claims includes technologies obtained by various modifications and alterations to the embodiments illustrated above.
[0089] As described above, the specific methods of the technology disclosed herein can be exemplified by the following items.
[0090] Item 1: A method for manufacturing a negative electrode, comprising:
[0091] The preparation process involves mixing graphite (as the negative electrode active material), Si-containing materials, a binder, and fibrous carbon materials in a dispersion medium containing at least water to prepare a negative electrode slurry; and
[0092] In the coating process, the above-mentioned negative electrode slurry is coated onto the negative electrode current collector to form a negative electrode composite material layer;
[0093] In this process, the negative electrode slurry is mixed with 10 times its mass of ion-exchanged water and centrifuged. The supernatant is collected and diluted 5 times its volume with ion-exchanged water to obtain a sample. The blackness is determined by multiplying the sum of absorbance at wavelengths of 600nm, 700nm, 800nm, and 900nm by 5 in the absorption spectrum of the sample measured at an optical path length of 25mm. In this preparation process, the negative electrode slurry is prepared to have a blackness of 30-65 and a shear rate of 100s. -1 The viscosity at that time was below 1100 mPa·s.
[0094] Item 2: The method for manufacturing the negative electrode according to Item 1, wherein the G / D ratio of the aforementioned fibrous carbon material based on laser Raman spectroscopy is 100 or less.
[0095] Item 3: The method for manufacturing the negative electrode according to Item 1 or 2, wherein the fibrous carbon material is a single-layer carbon nanotube.
[0096] Item 4: A method for manufacturing a negative electrode according to any one of items 1 to 3, wherein the solid content of the slurry during the above-mentioned mixing is set to 55% to 65% by mass.
[0097] Item 5: A method for manufacturing a negative electrode according to any one of items 1 to 4, wherein when the above-mentioned mixing is performed, and the negative electrode active material is set to 100 parts by mass, the proportion of the fibrous carbon material is 0.01 parts by mass to 0.1 parts by mass.
[0098] Item 6: A method for manufacturing a negative electrode according to any one of items 1 to 5, wherein when the negative electrode active material is set to 100 parts by mass in the negative electrode slurry, the proportion of the binder is 1 to 5 parts by mass.
[0099] Item 7: A method for manufacturing a negative electrode according to any one of items 1 to 6, wherein the viscosity of the negative electrode slurry is prepared to be 300 mPa·s to 600 mPa·s.
[0100] Item 8: A method for manufacturing a negative electrode according to any one of items 1 to 7, wherein, in the above-mentioned preparation step, a multi-shaft mixer is used to perform the above-mentioned mixing, and the mixing time is set to 90 seconds or less.
[0101] Item 9: A method for manufacturing an energy storage device, wherein an electrode body is made using a negative electrode obtained by the method for manufacturing a negative electrode according to any one of items 1 to 8, and the energy storage device is constructed using the aforementioned electrode body.
Claims
1. A method for manufacturing a negative electrode, comprising: The preparation process involves mixing graphite (as the negative electrode active material), Si-containing materials, a binder, and fibrous carbon materials in a dispersion medium containing at least water to prepare a negative electrode slurry; and In the coating process, the negative electrode slurry is coated onto the negative electrode current collector to form a negative electrode composite material layer; In this process, the negative electrode slurry is mixed with 10 times its mass of ion-exchanged water and centrifuged. The supernatant is collected and diluted 5 times its volume with ion-exchanged water to obtain a sample. The blackness is determined by multiplying the sum of the absorbance at wavelengths of 600nm, 700nm, 800nm, and 900nm by 5 in the absorption spectrum of the sample measured at an optical path length of 25mm. In the preparation process, the negative electrode slurry is prepared to have a blackness of 30-65 and a shear rate of 100s. -1 The viscosity at that time was below 1100 mPa·s.
2. The method for manufacturing the negative electrode according to claim 1, wherein, The fibrous carbon material has a G / D ratio of less than 100 based on laser Raman spectroscopy analysis.
3. The method for manufacturing the negative electrode according to claim 2, wherein, The fibrous carbon material is a single-layer carbon nanotube.
4. The method for manufacturing the negative electrode according to claim 1, wherein, The solid content of the slurry during the mixing process is set to 55% to 65% by mass.
5. The method for manufacturing the negative electrode according to claim 1, wherein, When the mixing process is carried out, if the negative electrode active material is set to 100 parts by mass, the proportion of the fibrous carbon material is 0.01 parts by mass to 0.1 parts by mass.
6. The method for manufacturing the negative electrode according to claim 1, wherein, In the negative electrode slurry, when the negative electrode active material is set to 100 parts by mass, the proportion of the binder is 1 to 5 parts by mass.
7. The method for manufacturing the negative electrode according to claim 1, wherein, The viscosity of the negative electrode slurry was prepared to be 300 mPa·s to 600 mPa·s.
8. The method for manufacturing the negative electrode according to claim 1, wherein, In the preparation process, a multi-shaft mixer is used for mixing, and the mixing time is set to less than 90 seconds.
9. A method for manufacturing an energy storage device, wherein, An electrode body is made using the negative electrode obtained by the manufacturing method of any one of claims 1 to 8, and an energy storage device is constructed using the electrode body.
Citation Information
Patent Citations
Anode
JP2020113485A
Anode slurry for lithium ion secondary battery and manufacturing method therefor
JP2023096785A